2005
DOI: 10.1007/s11244-005-2507-3
|View full text |Cite
|
Sign up to set email alerts
|

Catalysts Ru–CeO2/Sibunit for catalytic wet air oxidation of aniline and phenol

Abstract: Catalytic properties of carbon materials Sibunit (commercial samples) and ceria-promoted precious metals (Ru, Pt, Pd) supported on carbon were studied in the processes of catalytic wet air oxidation (CWAO) of aniline and phenol at elevated pressures and temperatures (T ¼ 433-473 K, P O2 ¼ 0.3-1.0 MPa). It was found that the activity increases when the catalyst is pretreated with hydrogen peroxide. An efficiency of Ru-CeO 2 /Sibunit catalyst with a low ruthenium content (~0.6% Ru) for deep cleaning of polluted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 23 publications
(36 reference statements)
0
10
0
Order By: Relevance
“…2). Our present and previous works [26,28,39] differ from the works by other authors [32][33][34][35][36][37][38]: before using carbon materials, we carefully washed them with an acid to remove surface metal impurities and controlled the contents of metals (Ni, Cu, Fe) on the surface of catalysts by XPS, and in the solution after the reaction by ICP-OES. Note that the contents of transition metals (Ni for N-CNFs and Sibunit, Cu for NCNFs, and Fe for Sibunit) in solutions after reactions did not exceed the contents of the same metals in blank experiments.…”
Section: The Catalytic Properties Of Carbon Supports Supported Ru Camentioning
confidence: 62%
See 1 more Smart Citation
“…2). Our present and previous works [26,28,39] differ from the works by other authors [32][33][34][35][36][37][38]: before using carbon materials, we carefully washed them with an acid to remove surface metal impurities and controlled the contents of metals (Ni, Cu, Fe) on the surface of catalysts by XPS, and in the solution after the reaction by ICP-OES. Note that the contents of transition metals (Ni for N-CNFs and Sibunit, Cu for NCNFs, and Fe for Sibunit) in solutions after reactions did not exceed the contents of the same metals in blank experiments.…”
Section: The Catalytic Properties Of Carbon Supports Supported Ru Camentioning
confidence: 62%
“…In a number of recent publications, it has been found that the commercial active carbons are highly active in wet air oxidation of phenol in the absence of supported active metals [32][33][34][35][36][37][38]. Therefore, at the beginning we tested N-CNFs and Sibunit in CWAO of phenol at a temperature of 160 • C and at a pressure of 50 bar.…”
Section: The Catalytic Properties Of Carbon Supports Supported Ru Camentioning
confidence: 99%
“…Sibunit material, which combines the properties of graphite (strength characteristics, corrosion resistance) and active carbons (developed surface, etc. ), is a suitable support for catalysts for liquid-phase oxidation processes [31][32][33].…”
Section: Catalytic Resultsmentioning
confidence: 99%
“…The modi-cation of supported Ru catalysts with secondary metals is oen effective in degradation of organic compounds. 22,35,36 The performance of Ru-M/Al 2 O 3 catalysts is shown in Fig. 2.…”
Section: Catalyst Optimization For Degradation Of Phenolmentioning
confidence: 99%